Tinjauan Hukum Islam terhadap Kerjasama Antara Pengemudi dan PT. Gojek Indonesia Cabang Madiun - Wahyu Ni'am Arrozi (Rechtsvinding, 2023)
This research departs from the practice of cooperation between drivers and PT. Gojek Indonesia, in which there is a withdrawal of attributes in the form of jackets and helmets as capital that has been purchased by the driver from the company. Also, the driver's balance will be forfeited when the partnership with the company ends, where the balance is an advantage that should have been owned by the driver. This is detrimental to the driver and profitable for the company. Collaboration between the driver and PT. Gojek Indonesia is a form of muamalah activity, namely musharakah and is included in the Shirkah Abdan category, because the two parties partner with capital and carry out joint efforts to get profits and are divided according to a mutual agreement. The aims of this study are: (1) to explain the review of Islamic law on the cooperation agreement between the driver and PT. Gojek Indonesia Madiun Branch. (2) Explain the review of Islamic law on the ownership of Gojek driver attributes. (3) Explain the review of Islamic law on the ownership of Gojek drivers' GoPay balances. According to its type, this research includes qualitative field research, namely seeking data directly into the field by looking closely at the object under study. The approach used in this study is a case study with data collection methods of interviews, observation, and documentation. Field data originating from administrators and drivers are then analyzed whether they are in accordance with Sharia Economic Law or not. From the data analysis it can be concluded that, (1) a review of Islamic law on the cooperation contract between the driver and PT. Gojek Indonesia's Madiun Branch is included in muamalah practices, namely Shirkah and is included in Shirkah 'Inan, where both parties partner with capital and do business for profit and are divided according to a mutual agreement. And that is legally permissible based on the Koran. (2) A review of Islamic law on ownership of Gojek driver attributes that the capital provided by the company to the driver is invalid because it does not comply with one of the requirements in capital, namely capital must be cash or cash and may not be owed. Regarding the withdrawal of attributes in the form of jackets and helmets when the driver's partnership with the company ends, it is not in accordance with the Shari'a. (3) A review of Islamic law on the ownership of Gojek drivers' GoPay balances, the driver's balance being forfeited due to a partner breaking up or freezing the balance by the company is contrary to Islamic law.